PERAN DPRD DALAM MENGAWASI KINERJA GUGUS TUGAS PERCEPATAN PENANGANAN (GTPP) COVID-19 PEMERINTAH KOTA MEDAN - muhammad Taufiqurrahman; Wong Chun Sen (JURNAL RETENTUM, 2020)
The Regional People's Representative Assembly's supervisory role aims at ensureing that all public policies related to the budget cycle are implemented in accordance with applicable laws and regulations and are oriented towards public priorities. As in the midst of the Covid-19 outbreak, budgeting and budget management no longer go through the discussion mechanism in the Regional People's Representative Assembly (DPRD) that is usually done. This is because the Regulation in Lieu of a Law (Perpu) for handling the Corona Virus makes the Regional Government (Pemda) have the authority to regulate the budget at will. To be sure, the potential for misuse of the state budget in handling the Covid-19 outbreak is prone to be occured.